PENGARUH MODEL PEMBELAJARAN POLYA PROBLEM SOLVING TECHNIQUE (POPSOT) TERHADAP KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK KELAS XI PADA MATERI GELOMBANG BUNYI DI SMA NEGERI 12 BULUKUMBA - Nisa Syam, Niswatul; H. Sudirman; Jusman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to: (1) describe the critical thinking skills of students taught using the Polya Problem Solving Technique; (2) describe the critical thinking skills of students taught using a conventional learning model; and (3) analyze the differences between the two groups on sound wave material at State Senior High School 12 Bulukumba. This research is a quasi-experimental study with a quantitative approach using a Matching Only Posttest-Only Control Group Design. The population includes all 11th-grade students, while the sample was selected through a two-step matching sampling technique, resulting in two classes: class XI D as the experimental group and class XI A as the control group. The research instrument was a validated multiple-choice test consisting of 20 items measuring critical thinking skills. Data analysis was conducted both descriptively and inferentially, including tests of normality, homogeneity, and hypothesis testing. Descriptive results showed that students in the experimental class achieved very high critical thinking skills with an average score of 81.76, a minimum of 60, and a maximum of 100. In contrast, the control class was categorized as high, with an average score of 70.00, a minimum of 45, and a maximum of 95. The hypothesis test using an independent samples t-test obtained a significance value (two-tailed) of 0.013, which is less than 0.05. Thus, H0 is rejected and H1 is accepted, indicating a significant difference between the two groups. Therefore, the Polya Problem Solving Technique has a positive effect on students’ critical thinking skills and can be used as a reference for future research.